Triple sum

Calculus Level 5

S = i = 0 j = 0 k = 0 1 5 i + j + k , i j k , i k \large S= \sum^{\infty}_{i=0}\sum^{\infty}_{j=0}\sum^{\infty}_{k=0} \dfrac{1}{5^{i+j+k}}, \quad i≠j≠k, i≠k If the value of S S is in the form a b \dfrac{a}{b} , where a a and b b are coprime positive integers, then find a + b a+b .


The answer is 2109.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tapas Mazumdar
May 5, 2017

First observe that

1 5 i + j + k = 1 5 i 5 j 5 k \dfrac{1}{5^{i+j+k}} = \dfrac{1}{5^i 5^j 5^k}

Now we break down the sum into three separate sums as follows

S = i = 0 j = 0 k = 0 1 5 i 5 j 5 k ( i j k ) = i = 0 1 5 i S 1 S 1 = j = 0 , j i 1 5 j S 2 S 2 = k = 0 , k i , k j 1 5 k \begin{aligned} \displaystyle \bullet & \ S = \sum_{i=0}^{\infty} \sum_{j=0}^{\infty} \sum_{k=0}^{\infty} \dfrac{1}{5^i 5^j 5^k} (i \neq j \neq k) = \sum_{i=0}^{\infty} \dfrac{1}{5^i} \cdot S_1 \\ \displaystyle \bullet & \ S_1 = \sum_{j=0, \ j \neq i}^{\infty} \dfrac{1}{5^j} \cdot S_2 \\ \displaystyle \bullet & \ S_2 = \sum_{k=0, \ k \neq i, \ k \neq j}^{\infty} \dfrac{1}{5^k} \end{aligned}

Starting with S 2 S_2

S 2 = k = 0 , k i , k j 1 5 k = k = 0 1 5 k 1 5 i 1 5 j = 5 4 1 5 i 1 5 j \begin{aligned} \displaystyle S_2 &= \sum_{k=0, \ k \neq i, \ k \neq j}^{\infty} \dfrac{1}{5^k} \\ \displaystyle &= \sum_{k=0}^{\infty} \dfrac{1}{5^k} - \dfrac{1}{5^i} - \dfrac{1}{5^j} \\ \displaystyle &= \dfrac 54 - \dfrac{1}{5^i} - \dfrac{1}{5^j} \end{aligned}

Now

S 1 = j = 0 , j i 1 5 j S 2 = j = 0 , j i 1 5 j ( 5 4 1 5 i 1 5 j ) = ( 5 4 1 5 i ) j = 0 , j i 1 5 j j = 0 , j i 1 25 j = ( 5 4 1 5 i ) 2 ( 25 24 1 25 i ) = 25 48 5 2 1 5 i + 2 1 25 i \begin{aligned} \displaystyle S_1 &= \sum_{j=0, \ j \neq i}^{\infty} \dfrac{1}{5^j} \cdot S_2 \\ \displaystyle &= \sum_{j=0, \ j \neq i}^{\infty} \dfrac{1}{5^j} \left( \dfrac 54 - \dfrac{1}{5^i} - \dfrac{1}{5^j} \right) \\ \displaystyle &= \left( \dfrac 54 - \dfrac{1}{5^i} \right) \sum_{j=0, \ j \neq i}^{\infty} \dfrac{1}{5^j} - \sum_{j=0, \ j \neq i}^{\infty} \dfrac{1}{{25}^j} \\ \displaystyle &= {\left( \dfrac 54 - \dfrac{1}{5^i} \right)}^2 - \left( \dfrac {25}{24} - \dfrac{1}{{25}^i} \right) \\ \displaystyle &= \dfrac {25}{48} - \dfrac 52 \cdot \dfrac{1}{5^i} + 2 \cdot \dfrac{1}{{25}^i} \end{aligned}

Hence

S = i = 0 1 5 i S 1 = i = 0 1 5 i ( 25 48 5 2 1 5 i + 2 1 25 i ) = 25 48 i = 0 1 5 i 5 2 i = 0 1 25 i + 2 i = 0 1 125 i = 25 48 × 5 4 5 2 × 25 24 + 2 × 125 124 = 125 1984 \begin{aligned} \displaystyle S &= \sum_{i=0}^{\infty} \dfrac{1}{5^i} \cdot S_1 \\ \displaystyle &= \sum_{i=0}^{\infty} \dfrac{1}{5^i} \left( \dfrac{25}{48} - \dfrac 52 \cdot \dfrac{1}{5^i} + 2 \cdot \dfrac{1}{{25}^i} \right) \\ \displaystyle &= \dfrac{25}{48} \sum_{i=0}^{\infty} \dfrac{1}{5^i} - \dfrac 52 \sum_{i=0}^{\infty} \dfrac{1}{{25}^i} + 2 \sum_{i=0}^{\infty} \dfrac{1}{{125}^i} \\ \displaystyle &= \dfrac{25}{48} \times \dfrac 54 - \dfrac 52 \times \dfrac{25}{24} + 2 \times \dfrac{125}{124} \\ \displaystyle &= \dfrac{125}{1984} \end{aligned}

Thus, a b = 125 1984 a + b = 2109 \dfrac ab = \dfrac{125}{1984} \implies a+b = \boxed{2109} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...